2019
DOI: 10.1152/ajpgi.00331.2018
|View full text |Cite
|
Sign up to set email alerts
|

Translational and transcriptional responses in human primary hepatocytes under hypoxia

Abstract: The liver is the primary source of a large number of plasma proteins and plays a critical role in multiple biological processes. Inadequate oxygen supply characterizing various clinical settings such as liver transplantation exposes the liver to hypoxic conditions. Studies assessing hypoxia-induced global translational changes in liver are lacking. Here, we employed a recently developed ribosome-profiling technique to assess global translational responses of human primary hepatocytes exposed to acute hypoxic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 88 publications
1
12
0
Order By: Relevance
“…In this study we identified increased hypoxia gene signatures in a CHB cohort in the absence of cirrhosis or HCC. We confirmed hypoxic gene expression using MSigDB derived gene sets and recently reported signatures from HepG2 44 and PHH data sets 45 . We noted an increase in HIF-1α mRNA levels, consistent with their transcriptional regulation by inflammatory mediators such as TNFα.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In this study we identified increased hypoxia gene signatures in a CHB cohort in the absence of cirrhosis or HCC. We confirmed hypoxic gene expression using MSigDB derived gene sets and recently reported signatures from HepG2 44 and PHH data sets 45 . We noted an increase in HIF-1α mRNA levels, consistent with their transcriptional regulation by inflammatory mediators such as TNFα.…”
Section: Discussionsupporting
confidence: 69%
“…1b). To further validate these results, we analysed the acute transcriptional response of primary human hepatocytes (PHHs) 45 cultured under 1% oxygen for 4 h and identified 113 upregulated genes (FC > 2; FDR < 0.05) and GSEA showed an enrichment in CHB ( Supplementary Fig. 2a).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Ribosome profiling was conducted as described previously 7 using the Illumina TruSeq Ribo Profile (Mammalian) Kit according to manufacturer's instructions with modifications in harvest, RNA isolation/purification (isopropanol isolation used to improve the yield) and ribosome protected fragments size selection (~20-32 nt). During harvest, media was carefully removed, and cells were immediately flash-frozen.…”
Section: Ribosome Profilingmentioning
confidence: 99%
“…Since there are several other HEK293T ribosomal profiling datasets available, these could be used to examine the reproducibility of the results 6 . Furthermore, by looking into ribosome profiling datasets from other cell types, such as other human cells 7 and/or across species, it would be valuable to examine whether a given gene maintains the same translation kinetics or if there are significant differences that could reflect on the conformation of the protein. Clearly, since a rather large inter-experiment variation is expected, the accumulation of several ribosome profiling databases would be very useful for this type of analysis.…”
Section: Introductionmentioning
confidence: 99%